The Spectrum of Inborn Errors of Immunity in the United Arab Emirates: 5 Year Experience in a Tertiary Center - Shendi, Hiba Mohammed; Al Kuwaiti, Amna Ali; Al Dhaheri, Ahmed Darwaish; Al-Hammadi, Suleiman (Frontiers in Immunology, 2022)
Purpose Inborn Errors of Immunity (IEI) are heterogeneous disorders of immunity with variable clinical presentation and outcome. This is the first comprehensive report from the United Arab Emirates aiming to describe the demographics, clinical characteristics, categories, treatment modalities and outcome of patients with IEI. Methods This retrospective study was conducted on patients who attended Tawam Hospital between 2016-2020. Results We identified 162 patients with IEI, of whom 152 were children. The age of onset of symptoms ranged between birth to 38 years. About two-thirds of patients were Emirati nationals, 64.2% had consanguineous parents and 38.3% of cases were familial. Patients were classified as; immunodeficiencies affecting cellular and humoral immunity (20.4%), combined immunodeficiencies with associated or syndromic features (38.3%), predominantly antibody deficiencies (16%), immune dysregulation (4.3%), congenital defects of phagocytes number or function (8.6%), defects in intrinsic and innate immunity (1.9%) autoinflammatory disorders (1.9%), complement deficiency (6.2%), bone marrow failure (1.9%) and phenocopies of inborn errors of immunity (0.6%). Genetic testing was performed in 85.2% of patients with a diagnostic yield of 92.7%. Complications included bronchiectasis, neoplasia, and vaccine-related infections. Immunoglobulin therapy and antimicrobial prophylaxis were both used in (51.9%) of patients while (20.4%) underwent hematopoietic stem cell transplantation (HSCT). The overall mortality rate was 10.5%. Conclusion This report highlights the burden of IEI in the UAE. Ongoing education of physicians, establishment of a national registry and considering changes to early BCG vaccination are measures recommended to improve outcomes.